1994
DOI: 10.1038/npp.1994.8
|View full text |Cite
|
Sign up to set email alerts
|

Social Isolation in the Rat Produces Developmentally Specific Deficits in Prepulse Inhibition of the Acoustic Startle Response Without Disrupting Latent Inhibition

Abstract: A series of experiments examined the effects of 8 weeks of social isolation on spontaneous locomotor activity, prepulse inhibition (PPl) of the acoustic startle response, latent inhibition (LI) in a conditioned suppression paradigm, and basal and d-amphetamine stimulated dopamine (DA) release in the ventral striatum, as measured by in vivo microdialysis. Both isolation-reared animals (those isolated from the weaning age) and isolation-housed animals (those isolated as adults) were hyperactive when placed in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
153
1
8

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(176 citation statements)
references
References 35 publications
14
153
1
8
Order By: Relevance
“…Each of these models has both strengths and limitations; for example, SHR rats exhibit many of the behavioral characteristics of ADHD, but hypertension is a confounding factor in this model [79]. Isolation rearing may be a useful model because, in addition to the increased impulsivity noted in IC rats in the current study, IC rats are also hyperactive [13,26,47,80] and show attentional deficits [5,16,19,30,33,88,92] compared to EC rats. Further, in the current study, amphetamine decreased preservative non-reinforced responding in IC rats.…”
Section: Discussionmentioning
confidence: 91%
“…Each of these models has both strengths and limitations; for example, SHR rats exhibit many of the behavioral characteristics of ADHD, but hypertension is a confounding factor in this model [79]. Isolation rearing may be a useful model because, in addition to the increased impulsivity noted in IC rats in the current study, IC rats are also hyperactive [13,26,47,80] and show attentional deficits [5,16,19,30,33,88,92] compared to EC rats. Further, in the current study, amphetamine decreased preservative non-reinforced responding in IC rats.…”
Section: Discussionmentioning
confidence: 91%
“…Obviously, attentional and cognitive components of ADHD symptomatology may not be reflected by this model. It remains to be seen if PPI deficits induced by psychostimulants or dopaminergic overactivity (Wilkinson et al, 1994;Barr et al, 2004) reflect the sort of attentional deficits observed in ADHD. Nonetheless, it is interesting to note that selective serotonin reuptake inhibitors (SSRIs) are reported to be ineffective in ADHD (Findling, 1996), even though fluoxetine appears to reduce hyperactivity in DAT KO mice (Gainetdinov et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For example, isolation enhances mesolimbic function (Jones et al, 1992), resulting in increased dopamine and 5-HT function in the striatum (Jones et al, 1992;Wilkinson et al, 1994;Robbins et al, 1996;Fulford and Marsden, 1998;Hall et al, 1998), but reduces hippocampal, serotonergic and noradrenergic responsiveness (Wright et al, 1990(Wright et al, , 1991Bickerdike et al, 1993). Changes in hippocampal formation following isolation rearing may trigger compensatory changes within systems that depend on normal hippocampal input using glutamatergic transmission.…”
Section: Discussionmentioning
confidence: 99%